BERSINERGI UNTUK DESA: MAHASISWA KKN UNIVERSITAS COKROAMINOTO YOGYAKARTA DAN MASYARAKAT PADUKUHAN SINGOSAREN - Putri, Prihastini Oktasari; Antari, Ervin Dwi; Fifianawati, Fifianawati; Beni, Beni (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
The duration of this activity spanned approximately 4 weeks, starting from February 6th to March 6th, 2024. Padukuhan Singosaren was chosen as the location for KKN due to its rich village potential, which became the main focus for enhancing village development and the quality of Human Resources (HR) in utilizing and developing local potential. The KKN activity began with observations of the padukuhan to identify the village potential that would be the main focus of the KKN implementation. The programs designed were then arranged sequentially, starting from discussions among KKN groups, village apparatus, and the local community, especially those directly involved in the designed programs. The outcomes of the overall implementation of the KKN program encompass the development of community knowledge  through  various  educational and  socialization  activities  across  different layers of society, aiming to support development and enhance Human Resources (HR) to boost the potential of the local village. Literacy and learning programs, whether academic or religion-based, are conducted to enrich HR from an early age. In the environmental and planning sector, the development of drainage planning concepts and layouts is carried out in Padukuhan.